2019
DOI: 10.3390/polym11091446
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Polymer and Ceramic CAD/CAM Materials with Human Gingival Fibroblasts (HGFs)

Abstract: Four polymer and ceramic computer-aided design/computer-aided manufacturing (CAD/CAM) materials from different manufacturers (VITA CAD-Temp (polymethyl methacrylate, PMMA), Celtra Duo (zirconia-reinforced lithium silicate ceramic, ZLS), IPS e.max CAD (lithium disilicate (LS2)), and VITA YZ (yttrium-tetragonal zirconia polycrystal, Y-TZP)) were tested to evaluate the cytotoxic effects and collagen type I secretions on human gingival fibroblasts (HGFs). A total of 160 disc-shaped samples (Ø: 10 ± 2 mm; h: 2 mm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 75 publications
3
34
0
1
Order By: Relevance
“…Slight cytotoxicity was observed in the subtractive group. A similar study comparing the cytotoxicity of different polymer and ceramic CAD-CAM materials found that the prefabricated PMMA blank (VITA CAD-Tem) showed slight cytotoxicity on gingival fibroblasts after 72 hours [ 25 ]. Engler et al [ 24 ] investigated the residual monomer elution from different conventional and CAD-CAM dental polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Slight cytotoxicity was observed in the subtractive group. A similar study comparing the cytotoxicity of different polymer and ceramic CAD-CAM materials found that the prefabricated PMMA blank (VITA CAD-Tem) showed slight cytotoxicity on gingival fibroblasts after 72 hours [ 25 ]. Engler et al [ 24 ] investigated the residual monomer elution from different conventional and CAD-CAM dental polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Y-TZP is a ceramic core that has excellent biocompatibility [ 35 ] and mechanical strength such as hardness [ 36 ] and wear resistance [ 37 ], so it is widely used in the dental field [ 6 ]. However, the use of Y-TZP is limited due to poor bonding strength with resin cement.…”
Section: Discussionmentioning
confidence: 99%
“…Results show that after 72 h, all groups reached biologically acceptable levels of cytotoxic potential. Moreover, it is concluded that the ceramic materials (lithium disilicate) present a better cell response than the polymers [ 123 ].…”
Section: Biocompatibility and Cytotoxicity Of Cad/cam Materialsmentioning
confidence: 99%